Guidelines for the investigation of chronic diarrhoea in adults: British Society of Gastroenterology, 3rd edition - Arasaradnam, Ramesh P (Gut, 2018)
Chronic diarrhoea is a common problem, hence clear guidance on investigations is required. This is an updated guideline from 2003 for the investigations of chronic diarrhoea commissioned by the Clinical Services and Standards Committee of the British Society of Gastroenterology (BSG). This document has undergone significant revision in content through input by 13 members of the Guideline Development Group (GDG) representing various institutions. The GRADE system was used to appraise the quality of evidence and grading of recommendations.